Implementasi Akad Murabahah Dan Rahn Pada Produk Cicil Emas Di Bank Syari’ah Mandiri Kantor Cabang Pembantu Subang - Ai Siti Nurjadidah; Jalaludin; Ahmad Damiri (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2020)
This article was conducted with the aim to find out the murabahah and Rahn contract systems for the Gold Installment financing product, implementation of murabahah financing contract and rahn contract on Gold Installment financing products at Bank Syari’ah Mandiri KCP Subang and Benefits of the implementation of murabahah and rahn contracts in gold installment financing products at Bank Syariah Mandiri KCP Subang Sub-Branch Bank in 2019 descriptive method with qualitative data types. Data collection techniques are done by observation, interviews, and documentation studies. The primary sources are BSM Subang KCP employees, and Subang KSM BSM documents relating to the gold installment payment. Secondary data in the form of books about shariah economics, the internet, and other data that support this thesis. The results showed that the implementation of the gold installment product system in Subang KCP BSM was in accordance with Islamic shariah teachings. The problem that occurs is the lack of promotion or socialization held by the BSM regarding this gold installment product. The advice given to fix the problem faced is the need for various ways such as socialization with customers, because after researching the product in accordance with Islamic sharia. Keywords: Murabahah contract, Rahn contract, Gold installment